Zines for Research Exchange: A Conversation - Pasek, Anne; Biørn-Hansen, Aksel (Imaginations)

(untitled) (York University, 2025)
In this piece Anne Pasek and Aksel Biørn-Hansen interview each other on their respective experiments in zine-based experimental research exchange: DIY Methods, an annual conference-by-postal-mail, and Liminal Excavations, a zine-based intervention at ICT4S (Information and Communication Studies for Sustainability) 2024. They reflect on practical lessons they’ve learned in facilitating alternative publishing for academic research as well as some of the ways print helps make the environmental, cultural, and emotional character of scholarly norms both easier to analyze and contest.